Inhibitory substances produced by Streptococcus salivarius and colonization of the upper respiratory tract with group A streptococci. - Huskins, W. C. (Cambridge University Press, 1989)
It has been proposed that inhibitory substances produced by viridans streptococci colonizing the upper respiratory tract aid in eradication of established group A streptococcal colonization of that site. We studied the prevalence of inhibitory-substance producing strains of Streptococcus salivarius in throat cultures from three groups of children: 16 children with persistently positive throat cultures for group A streptococci despite receiving recommended therapeutic courses of antibiotics (group I), 26 children from whom group A streptococci were eradicated from the upper respiratory tract by antibiotic therapy (group II), and 18 children who never harboured group A streptococci in their upper respiratory tract during the study period (group III). An in vitro deferred antagonism method was employed to detect inhibitory substances; 5233 strains of S. salivarius were examined. Strains of S. salivarius producing inhibitory substances were isolated from 76-88% of the children in each group on at least one occasion. However, only a small percentage of subjects in each group harboured strains producing these substances in every throat culture. The mean total percentage of S. salivarius strains producing inhibitory substances was 21.8% in children in group I, 22.4% in children in group II, and 16.4% in children in group III; these percentages were not statistically different (P greater than 0.1). In this study, we could not confirm a significant role for inhibitory substances produced by S. salivarius in the eradication of group A streptococci from the upper respiratory tract of colonized individuals.